1990
DOI: 10.1177/0893318990004002003
|View full text |Cite
|
Sign up to set email alerts
|

The Richness Imperative and Cognitive Style

Abstract: This article proposes a new thesis about the role of individual differences in managers' media choice behavior. It argues that individual differences influence media choice only under conditions of low message equivocality. When equivocality is high, a “richness imperative” masks the influence of individual differences. Managers are compelled to use richer media to match the equivocality of the message. However, in low-equivocality situations, richness demands are lowered. Any medium is capable of carrying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Our analysis of e-mail practices has presented the argument that users are fluent e-mail communicators, adept at turning this medium to their evolving needs. The ways in which they do so today are surprisingly nonproblematic in the light of much of the early research literature (e.g., Daft & Lengel, 1984;Trevino et al, 1990), which tended to focus on the shortcomings of e-mail as a communication tool. In the final part of this article we suggest a number of potential design innovations that could capitalize on or better support these practices in relation to talking about objects.…”
Section: Changing the Way We Talkmentioning
confidence: 98%
See 1 more Smart Citation
“…Our analysis of e-mail practices has presented the argument that users are fluent e-mail communicators, adept at turning this medium to their evolving needs. The ways in which they do so today are surprisingly nonproblematic in the light of much of the early research literature (e.g., Daft & Lengel, 1984;Trevino et al, 1990), which tended to focus on the shortcomings of e-mail as a communication tool. In the final part of this article we suggest a number of potential design innovations that could capitalize on or better support these practices in relation to talking about objects.…”
Section: Changing the Way We Talkmentioning
confidence: 98%
“…tings (e.g., Daft & Lengel, 1984;Trevino, Lengel, Bodenstein, Gerloff, & Muir, 1990), there is usually enough shared context among collaborators to make overly explicit and heavyweight textual reference unnecessary. In other words, e-mail conversations are grounded in sufficient mutual knowledge (Clark, 1992) to allow very brief, sketchy, and implicit references to succeed without posing significant problems in interpretation.…”
Section: References and Common Groundingmentioning
confidence: 99%
“…Intolerance of ambiguity was originally defined as a general tendency to perceive ambiguous material or situations as threatening. 49 Trevino et al 50 found tolerance of ambiguity an important individual difference influencing preferences for rich or lean channels of communication. Kahn et al 5 found role ambiguity an important source of stress for people in work organizations and personality an important intervening variable between environmental stress and individual strain.…”
Section: Adaptationmentioning
confidence: 99%
“…Not all communication mechanisms, however, are equally effective or efficient. A continuum of media richness has been proposed for various modern modes of communication ranging from person to person meetings to standardized data transfer, such as electronic data interchange (Trevino et al, 1990;Sitkin, Sutcliffe, and Barrios-Choplin, 1992). Lengel and Daft (1988), found that a match must exist between the communication mode and the degree routine of a task.…”
Section: Communicationmentioning
confidence: 99%